Data on draft genomes and transcriptomes from females and males of the flour moth, Ephestia kuehniella - Axel Künstner; Hauke Busch; Enno Hartmann; Walther Traut (Data in Brief, 2022)
We present genomes and pupal transcriptomes of the Mediterranean flour moth, Ephestia kuehniella. The moth is a world-wide storage pest as well as a laboratory species with a considerable background in developmental biology, genetics, and cytogenetics. The sequence data were derived from a highly inbred laboratory strain and, hence, display very little heterozygosity. Female and male genomes and transcriptomes are represented separately in two sets each of raw and assembled sequence data. They are designed as a basis to develop new strategies in pest control, to elucidate the molecular adaptation for its peculiar lifestyle, and for research on sex chromosome structure, sex determination and sex-specific gene activity. For a test, all genes known or suspected to have a role in sex determination were extracted from the data. Raw sequencing data and assemblies are available at European Nucleotide Archive under accession number PRJEB49052.